Letters to Nicole - Smith, Tim, 1954- (Wheaton, Ill. : Tyndale House Publishers, 1995)
Thirty letters from a father to his twelve-year-old daughter on such issues as expectations, self-esteem, emotions, sexuality, and spiritual growth.
Includes indexes.
Keywords: Fathers and daughters -- Juvenile literature; Parent and teenager -- Religious aspects -- Christianity -- Juvenile literature; Fathers and daughters; Conduct of life; Christian life